Complement factor H in its alternative identity as adrenomedullin-binding protein 1. Issue 1 (November 2015) - Sim, Robert B.; Ferluga, Janez; Al-Rashidi, Hanan; Abbow, Hussein; Schwaeble, Wilhelm; Kishore, Uday
Highlights: Complement factor H has another role outside the complement system. It binds and stabilises adrenomedullin, with unusual binding characteristics. Adrenomedullin and factor H have been coadministered as potential therapeutics in animal disease models. Abstract: Complement factor H has been extensively studied since its discovery 50 years ago, and its role in the complement system is quite well established. It has another role, however, as a binding protein for the regulatory peptide adrenomedullin. Part of this role appears to be protection of adrenomedullin from proteolytic degradation. The binding interaction is unusual and merits further investigation. Adrenomedullin has potential therapeutic uses in diseases affecting the vasculature, and factor H has been administered with adrenomedullin in some animal models of disease.